Platform-Driven Misrepresentation of Muslim Women on Instagram: Religious Commodification in Indonesia’s Beauty Industry - Refti Handini Listyani; Yuniar Galuh Larasati; Najah Nadiah Amran; Annisa Dwi Lestari (Jurnal Ilmiah Peuradeun, 2026)
Instagram has become a major platform shaping the visibility of Muslim women in Indonesia’s beauty industry, where aesthetic appeal, religious symbolism, and commercial promotion are closely connected. Existing studies have discussed Muslim women’s identity performance, modest fashion, and influencer culture, but limited attention has been given to how misrepresentation is systematically produced through visual and discursive practices. This study aims to analyse how Muslim women are represented through the intersection of objectification and religious commodification within Instagram’s influencer economy. Using qualitative Critical Discourse Analysis, this study examines Instagram posts from five Indonesian Muslim women influencers, including images, captions, and audience interactions. The analysis reveals that physical appearance and religious identity function simultaneously as marketable resources, positioning Muslim women as aesthetic objects and symbolic carriers of religiosity in promotional practices. Beauty, modest fashion, luxury consumption, and domestic roles dominate representation, while intellectual and socio-cultural contributions receive limited visibility. This pattern indicates that misrepresentation is driven by platform visibility regimes, algorithmic selection, and commercial imperatives that transform religiosity into digital labour and reinforce gender inequality in digital environments.